"Arm-first" approach for the synthesis of star-shaped stereoregular polymers through living coordination polymerization. Issue 9 (9th February 2017) - Shi, Zhenghai; Guo, Fang; Tan, Rui; Niu, Hui; Li, Tingting; Li, Yang
Abstract : Stereoregular star polymers were synthesized through an "arm-first" approach via a living coordination polymerization mechanism for the first time using a half-sandwich scandium catalyst system. Abstract : The synthesis of stereoregular star polymers, including star cis -1, 4-PB, star cis -1, 4-PB- ran -3, 4-PI and star cis -1, 4-PB- b-syn -PS, through an "arm-first" approach via a living coordination polymerization mechanism is reported in this work for the first time. The half-sandwich scandium catalyst (C5 Me4 SiMe3 )Sc(CH2 SiMe3 )2 (THF) activated with [Ph3 C][B(C6 F5 )4 ] is used herein. Star cis -1, 4-PB compounds with various arm lengths and arm numbers ranging from 1.0 × 10 4 to 6.5 × 10 4 g mol −1 and 7.6 to 26.4, respectively, are produced by tuning the polymerization parameters. Additionally, the stereoregular star cis -1, 4-PB- ran -3, 4-PI and star cis -1, 4-PB- b-syn -PS are also explored in the same way with average arm numbers of 21.4 and 16.5 and 35% and 41% star yield, respectively.